PENGUJIAN TRICHO-KOMPOS LIMBAH JAGUNG DALAM MENINGKATKAN PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aimed to examine the effect of Trichocompost corn wasted to the growth and production of mustard. This research has been conducted on the experimental farm of the Faculty of Agriculture, Riau University. This study was conducted from April to May 2016. This study was performed experimentally using by Randomized Block Design (RBD) consisting of 5 treatments were t0: Non Trichocompost Corn Waste, t1: 0.75 kg/plot Trichocompost Corn Waste, t2: 1.5 kg/plot Trichocompost Corn Waste, t3: 2.25 kg/plot Trichocompost Corn Waste, and t4: 3.00 kg/plot Trichocompost Corn Waste. Each treatment was repeated 4 times and 4 samples plant taken from each plot. Parameters observed were plant height (cm), number of leave (blade), leaf area (cm2), fresh weight (g) and fresh weight feasible consumption (g). The results showed that The Trichocompost corn waste can improve plant growth, especially height, number of leave, leaf area, fresh weight and fresh weight worth of consumption. Â Keywords : Trichocompost Corn Waste, Mustard (Brassica juncea L.)